MEMBANGUN PENDIDIKAN BERBASIS ENTREPRENEUR - Wadhan - (TADRIS: Jurnal Pendidikan Islam, 2009)
Entrepreneur education is a kind of educational services to reach the national education goals. Entrepreneur education supports and strenghthens the realization of whole persons as the nation and government programmed. Entrepreneur education helps succeeding the national education objectives accordingly to Pancasila (the five principles of national ideology). As the consequence, entrepreneur education and national education are nor separable because both supports and endeavos to achieve the national education goals.